Penerapan Asas Proporsionalitas dalam Penjatuhan Sanksi Pidana terhadap Pelaku Tindak Pidana Korupsi: Putusan No. 29/Pid.Sus-TPK/2021/PN.JKT.PST - Aretha Aurora (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Corruption is classified as an extraordinary crime that causes extensive harm to state finances and public welfare, particularly when committed during national emergencies. This study analyzes the application of the principle of proportionality in sentencing corruption offenders through Decision Number 29/Pid.Sus-TPK/2021/PN.JKT.PST concerning the corruption of Covid-19 social assistance funds involving the former Minister of Social Affairs, Juliari Batubara. Employing a normative legal research method with statutory, conceptual, and case approaches, this article examines whether the imposed sentence reflects the seriousness of the offense, the scale of state losses, and the extraordinary circumstances of a national disaster. The analysis reveals that the court failed to optimally apply the principle of proportionality by not considering Article 2 paragraph (2) of the Anti-Corruption Law, which allows aggravated punishment in specific conditions. This study contributes to the development of proportionality-based sentencing discourse and emphasizes the need for stronger judicial reasoning to ensure substantive justice and deterrence in corruption cases with significant social impact.